2017
DOI: 10.1161/jaha.117.005602
|View full text |Cite
|
Sign up to set email alerts
|

Reoxygenation Reverses Hypoxic Pulmonary Arterial Remodeling by Inducing Smooth Muscle Cell Apoptosis via Reactive Oxygen Species–Mediated Mitochondrial Dysfunction

Abstract: BackgroundPulmonary arterial remodeling, a main characteristic of hypoxic pulmonary hypertension, can gradually reverse once oxygen has been restored. Previous studies documented that apoptosis increased markedly during the reversal of remodeled pulmonary arteries, but the types of cells and mechanisms related to the apoptosis have remained elusive. This study aimed to determine whether pulmonary artery smooth muscle cell (PASMC)‐specific apoptosis was involved in the reoxygenation‐induced reversal of hypoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 58 publications
5
28
0
Order By: Relevance
“…Ischemia-reperfusion injury-induced apoptosis ordinarily accompanies high levels of ROS production 45. Excessive ROS levels can increase the permeability of the inner mitochondrial membrane and disturb the balance of Bcl-2-like anti-apoptotic factors and Bax-like pro-apoptotic factors, resulting in the release of pro-apoptotic proteins, such as CYC, into the intermembrane space 46. Release of CYC activates CASP3, which can induce apoptosis 47.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-reperfusion injury-induced apoptosis ordinarily accompanies high levels of ROS production 45. Excessive ROS levels can increase the permeability of the inner mitochondrial membrane and disturb the balance of Bcl-2-like anti-apoptotic factors and Bax-like pro-apoptotic factors, resulting in the release of pro-apoptotic proteins, such as CYC, into the intermembrane space 46. Release of CYC activates CASP3, which can induce apoptosis 47.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria, which are organelles that are present in all cells of the human body except erythrocytes, play a pivotal role in energy production (Caja and Enriquez 2017;Vendrov et al 2017). In addition to this vital function, mitochondria are involved in other complex processes, such as cellular energy metabolism, oxidative stress regulation, calcium signaling modification, cellular proliferation, and cellular death (especially mitochondria-dependent caspase 9 apoptosis) (Chen et al 2017;Wang et al 2017a;Zhou et al 2014Zhou et al , 2015a. Notably, previous studies have indicated that endothelial viability under high-fat stimulation is related to mitochondrial apoptosis (Chattopadhyay et al 2017;Zhang et al 2016;Zhou et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that PHT causes neuronal apoptosis (Bittigau et al, 2002;Zhao et al, 2003). Apoptosis refers to a form of cell death controlled by genes, regulates the development of the body and maintains the stability of the internal environment (Abeti et al, 2016;Chen et al, 2017;Gahl et al, 2016;Han et al, 2018). Studies have shown that neuronal apoptosis is a key event in the pathogenesis of epilepsy, cerebral ischemia and other diseases (Abiega et al, 2016;Dai et al, 2018;Li et al, 2017;Singh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%